PENERAPAN PEMBELAJARAN MODIFIKASI LOMPAT DENGAN BAN UNTUK MENINGKATKAN HASIL BELAJAR LOMPAT JAUH PADA SISWA KELAS V SDK LEWOLOBA KABUPATEN FLORES TIMUR - Tokan, Antonius (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
Infrastructure that is owned on average is only a landing tub with a minimalist size and a free area for taking the start of a running start in doing jumping activities is less than ideal. This happened not because the school was unwilling and unable to provide it, but because of the limited land available for the field. However, the learning process will be carried out well, if the teachers can modify the facilities and infrastructure, so that the objectives of learning can be achieved. Seeing the condition of the low achievement or student learning outcomes of class V on the material jumping style Bouncy (Schnepper), several attempts have been made by the writer both as a researcher and as the phisycal education teacher in class V SDK Lewoloba. One of them is to work with Penjasorkes teacher friends in a group or allied group to improve the quality of learning in the classroom by applying the learning of tire jump modification to students. With the tire jump modification learning, students are expected to be able to carry out long jump learning with a different atmosphere, more comfortable, relaxed, but possible to improve their learning outcomes. The formulation of the problem in this research is whether there is an increase in Long Jump Learning Outcomes through the modification of the Jump Jump Learning for Class V Students of Lewoloba SDK School year 2018/2019 ?. The purpose of this study was to find out the improvement of Long Jump Learning Outcomes through the modification of Ban Jump Learning for Class V Students of Lewoloba SDK 2018/2019 Academic Year. The research method used was classroom action research (CAR). The population and sample used were students of class v SDK Lewoloba, totaling 20 students. The results of the study in the first cycle showed that the percentage of students viewed from the classical completeness formula was: KK = 13 / (20) x 100% = 65%. So students who get a minimum score of 70 is 65%, this means the research indicators have not reached classical completeness so it needs to be continued in the second cycle where the result is the percentage of students viewed from the classical completeness formula are: KK = 18 / (20) x 100% = 90% . So students who score at least 70 are 90%. This means that the research indicators have reached classical completeness. This can be seen from the minimum completeness criteria in the Application of Learning to Modify Jump with Tires to Improve Learning Outcomes of Long Jump in Class V Students of Lewoloba SDK, Ile Mandiri District, East Flores Regency, Academic Year 2018/2019 with individual completeness is â‰¥ 70 and classical completeness â‰¥ 90%.